Communities and Museums in the 21st Century : Shared Histories and Climate Action. - Brown, Karen; Cummins, Alissandra; González Rueda, Ana S. (Milton : Taylor & Francis Group, 2023)
Communities and Museums in the 21st Century brings together innovative, multidisciplinary perspectives on contemporary museology and participatory museum practice that contribute to wider debates on museum communities, heritage, and sustainability.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books